Angels or Demons: A Comparative Analysis of Motherhood Concept in World Literature - Senem Üstün Kaya (Akademik Dil ve Edebiyat Dergisi, 2026)
From the beginning of the history of humanity, motherhood has been considered as the most sacred and constant attribute in many cultures. During periods, although women’s roles and responsibilities have changed due to the social, politic and economic events, the main responsibility of a woman has always been accepted as ‘‘motherhood’’. With the modern era, as women participated in social spheres, mothering has been shaped in terms of expectations and prejudices. Motherhood has evolved through ages, yet, the expected notions of mothers mirror and recall similar attributes in almost all cultures: patience, self-sacrifice, compassion, charity and unconditional love towards children. There are various conducted studies based on the concept of ‘‘motherhood’’ in psychology, anthropology and literature. However, for this study, in order to exemplify the concept of ‘‘motherhood’’ defined by Adrienne Rich in her work Of Woman Born (1976), certain mother figures from the literary texts of world literature were chosen and comparatively analyzed. The aim of this study was not to generalize the concept of “motherhood” for every culture in world literature, yet, based on the findings of the analysis, it was observed that the perception of ‘‘motherhood’’ has been reflected in similar ways in many literary works of different cultures. Therefore, this study is exemplarily for further comparative literary studies based on motherhood and mothering in world literatures.